2011
DOI: 10.1375/twin.14.1.64
|View full text |Cite
|
Sign up to set email alerts
|

Strong Genetic Correlation Between Interview-Assessed Internalizing Disorders and a Brief Self-Report Symptom Scale

Abstract: Self-report scales for symptoms of anxiety and depression are frequently used for screening and research purposes. A moderate phenotypic association between disorders measured by diagnostic interviews and symptoms of anxiety and depression measured by self-report scales has been shown, but little is known about the overlap in these phenotypes' genetic and environmental variance. In the present study, we used twin modeling to identify common genetic and environmental liabilities underlying the phenotypic associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 54 publications
2
19
1
Order By: Relevance
“…To our knowledge, this was the first study that reported the genetic correlations between current smoking and current drinking in China. These measures were categorically defined, so the bivariate threshold genetic model was used (Gjerde et al, 2011). Undoubtedly, cigarette smoking was obviously influenced by genetic factors and not significantly by shared environmental effects, which was consistent with that reported in adult twins of Western origin Madden et al, 2004;True et al, 1997).…”
Section: Discussionsupporting
confidence: 60%
“…To our knowledge, this was the first study that reported the genetic correlations between current smoking and current drinking in China. These measures were categorically defined, so the bivariate threshold genetic model was used (Gjerde et al, 2011). Undoubtedly, cigarette smoking was obviously influenced by genetic factors and not significantly by shared environmental effects, which was consistent with that reported in adult twins of Western origin Madden et al, 2004;True et al, 1997).…”
Section: Discussionsupporting
confidence: 60%
“…Second, there could be health differences between twins and singletons. However, other twin samples have been found to be representative for the general population regarding several health, lifestyle, and personality measures (Andrew et al, 2001;Johnson et al, 2002), and the prevalence of mental disorders is approximately the same in our sample as other population-based studies (Gjerde et al, 2011;Kessler et al, 2005a). Third, the diagnostic interviews were conducted early in the follow-up period and could thus to some degree reflect consequences of sick leave.…”
Section: Methodological Considerationsmentioning
confidence: 83%
“…Genetic risk factors are primarily shared for internalizing disorders and psychological distress (Gjerde et al, 2011). There is also a familial aggregation of sick leave.…”
mentioning
confidence: 99%
“…The participants were asked to what extent a set of statements, covering the last 2 weeks, are true on a 1 ('not bothered') to 4 ('very bothered') scale. It has previously been shown that the genetic correlation between SCL-5 and mood disorders measured by the Composite International Diagnostic Interview was close to 1.0, suggesting that the genetic risk for depression can be captured by just five items (Gjerde et al, 2011). We calculated mean-scores for each individual for each time-point.…”
Section: Methodsmentioning
confidence: 99%